2013
DOI: 10.1016/j.spa.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

On the supremum ofγ-reflected processes with fractional Brownian motion as input

Abstract: Let {X H (t), t ≥ 0} be a fractional Brownian motion with Hurst index H ∈ (0, 1] and define a γ-In this paper we establish the exact tail asymptotic behaviour of M γ (T ) = sup t∈[0,T ] W γ (t) for any T ∈ (0, ∞].Furthermore, we derive the exact tail asymptotic behaviour of the supremum of certain non-homogeneous mean-zero Gaussian random fields.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 14 publications
3
46
0
Order By: Relevance
“…In this paper we analyze 0-1 properties of a class of such processes, that due to its importance in queueing theory (and dual risk theory) gained substantial interest; see, e.g., Norros (2004), Piterbarg (2001), Asmussen (2003), and Asmussen and Albrecher (2010) or novel works on γ -reflected Gaussian processes (Hashorva et al 2013;Liu et al 2015).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In this paper we analyze 0-1 properties of a class of such processes, that due to its importance in queueing theory (and dual risk theory) gained substantial interest; see, e.g., Norros (2004), Piterbarg (2001), Asmussen (2003), and Asmussen and Albrecher (2010) or novel works on γ -reflected Gaussian processes (Hashorva et al 2013;Liu et al 2015).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…With motivation from the aforementioned contributions, this paper is concerned with the Gaussian approximation of the random vector (τ * 1 (u), τ * 2 (u)). For the derivation of the tail asymptotics of sup t∈[0,T ] W γ (t), Hashorva et al (2013) showed that the investigation of the supremum of certain nonstationary Gaussian random fields is crucial. One key merit of our problem of approximating the joint distribution function of (τ * 1 (u), τ * 2 (u)) is that it leads, as in the case of the analysis of the tail asymptotics of sup t∈[0,T ] W γ (t), to an interesting unsolved problem of asymptotic theory of Gaussian random fields.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The shape of Lemma 1 is tailored to the needs of the next section, where asymptotics of tail distribution of inf sup functionals of Gaussian processes are analyzed. Various further extensions of Lemma 1 can be thought of along the lines of already existing extensions of the classical Pickands' lemma, especially in the direction allowing nonconstant variance function of the family (X u ), as in Piterbarg and Prisyazhnyuk (1978) or Hashorva et al (2013).…”
Section: Centered Gaussian Field With a Constant Variance Equal To Onmentioning
confidence: 99%
“…In this paper we analyze the asymptotic properties of tail distribution of infimum of an important class of such processes, that naturally appear in models of storage (queueing) systems and, by duality to ruin problems, gained broad interest also in problems arising in finance and insurance risk; see, e.g., Norros (2004), Piterbarg (2001), Asmussen (2003), and Asmussen and Albrecher (2010) or a novel work (Hashorva et al 2013).…”
Section: Introductionmentioning
confidence: 99%